Heat-related Changes of Density, P-wave Velocity, and Surface Hardness of Granite - Németh, Andor; Török, Ákos (Periodica Polytechnica Civil Engineering, 2021)
Low- and intermediate-level radioactive waste is stored in the National Radioactive Waste Repository in Bátaapáti in Hungary. The repository is located in the Carboniferous Mórágy Granite Formation. This paper focuses on heat-related changes of physical properties such as bulk density, P-wave velocity, P-wave modulus, and Duroskop surface hardness of the dominant lithology: monzogranite. Cylindrical specimens were tested at laboratory conditions (22 °C) and were heat-treated up to 250 °C, 500 °C, and 750 °C. The properties were measured before and after the thermal strain. After heat-treatment, the monzogranite samples became brownish, and at 750 °C, cracks appear at the surface of the specimens. Laboratory test results show that bulk density values slightly decrease from room temperature to 250 °C treatment and further dropped at 500 °C and especially at 750 °C. P-wave velocity values and the connected P-wave modulus tend to decrease from room temperature to 750 °C significantly. Duroskop rebound values show slight declines in the surface strength of the specimens until 500 °C, and then a drastic decline at 750 °C. Heat treatment tends to alter the physical properties of the monzogranite. From room temperature to 500 °C, a slight but apparent decrease between 500 °C and 750 °C significant reductions in the bulk density, P-wave velocity, and Duroskop values. Behind the physical alterations are the different thermal-induced expansion of minerals and mineral alteration at elevated temperatures.